ANALISIS KESULITAN BELAJAR SISWA SMP KELAS VII PADA MATERI HIMPUNAN - Indriani Lestari; Tina Rosyana; Luvy Sylviana Zanthy (IKIP Siliwangi, 2022)
Learning difficulties are external factors that have an impact on the low learning outcomes of students in mathematics. Another element that adds to learning difficulties is the lack of enthusiasm (motivation) for learning and makes students reluctant and lazy to learn mathematics. The reasons for carrying out the analysis of this study include finding, identifying and assessing learning difficulties faced by class VII students at SMP Negeri 1 Cililin, as well as students' mistakes when working on set material questions. The method used in this research is by using descriptive qualitative method. Participants in this study were 18 students. The approach of collecting data in this research is by giving a test test of three questions in the form of a description. Based on the money study that has been carried out, there are several aspects of learning difficulties including although most students already understand the concept of the set, they still experience some learning difficulties, such as not being able to understand the problem, not being careful in recording the members of the set, and having difficulty in making the required mathematical model.